Neuromuscular Factors Contributing to Reductions in Muscle Force After Repeated, High-Intensity Muscular Efforts - Kirk, Benjamin J. C.; Trajano, Gabriel S.; Pulverenti, Timothy S.; Rowe, Grant; Blazevich, Anthony J. (Frontiers in Physiology, 2019)
Multiple neuromuscular processes contribute to the loss of force production following repeated, high-intensity muscular efforts, however the relative contribution of each process is unclear. In Experiment 1, 16 resistance trained men performed 6 sets of unilateral isometric plantarflexor contractions of the right leg (3 s contraction/2 s rest; 85% maximal voluntary contraction torque; 90-s inter-set rest) until failure with and without caffeine ingestion (3 mg·kg-1) on two separate days. Corticospinal excitability and cortical silent period (cSP) were assessed before and immediately, 10 min and 20 min after the exercise. In Experiment 2, electrically-evoked tetanic force and persistent inward current (PIC)-mediated facilitation of the motor neuron pool (estimated using neuromuscular electrical stimulation with tendon vibration) were assessed before and after the same exercise intervention in 17 resistance trained men. Results showed decreases in peak plantar flexion torque (Experiment 1; -12.2%, Experiment 2; -16.9%), electrically-evoked torque (20 Hz -15.3%, 80 Hz -15.3%, variable-frequency train -17.9%) and cSP (-3.8%; i.e. reduced inhibition) post-exercise which did not recover by 20 min. Electromyographic activity (EMG; -6%), corticospinal excitability (-9%) and PIC facilitation (-24.8%) were also reduced post-exercise but recovered by 10 min. Caffeine ingestion increased torque and EMG but did not notably affect corticospinal excitability, PIC amplification or electrically-evoked torque. The data indicate that a decrease in muscle function largely underpins the loss of force after repeated, high-intensity muscular efforts, but that the loss is exacerbated immediately after the exercise by simultaneous decreases in corticospinal excitability and PIC amplitudes at the motor neuron.